Sarcoidosis following alemtuzumab treatment for multiple sclerosis. (November 2018) - Willis, Mark D; Hope-Gill, Ben; Flood-Page, Patrick; Joseph, Fady; Needham, Ed; Jones, Joanne; Coles, Alasdair; Robertson, Neil P
Despite proven efficacy of alemtuzumab in multiple sclerosis (MS), approximately 50% of individuals will develop a new autoimmune disease following treatment. To date, these have largely been antibody mediated and organ specific (primarily affecting the thyroid gland). In a retrospective case series of 187 patients from two UK specialist centres (Cardiff and Cambridge) followed up for a median of 10 years, we report three (1.6%) cases of sarcoidosis following alemtuzumab treatment of MS. This report increases the spectrum of auto-inflammatory disease following alemtuzumab and should be considered by clinicians when using this therapeutic agent for MS.